Gene expression plasticity facilitates different host feeding in Ips sexdentatus (Coleoptera: Curculionidae: Scolytinae) - Sellamuthu, Gothandapani; Naseer, Aisha; Hradecký, Jaromír; Chakraborty, Amrita; Synek, Jiří; Modlinger, Roman; Roy, Amit (Insect biochemistry and molecular biology, 2024)
Host shift is ecologically advantageous and a crucial driver for herbivore insect speciation. Insects on the non-native host obtain enemy-free space and confront reduced competition, but they must adapt to survive. Such signatures of adaptations can often be detected at the gene expression level. It is astonishing how bark beetles cope with distinct chemical environments while feeding on various conifers. Hence, we aim to disentangle the six-toothed bark beetle (Ips sexdentatus) response against two different conifer defences upon host shift (Scots pine to Norway spruce). We conducted bioassay and metabolomic analysis followed by RNA-seq experiments to comprehend the beetle's ability to surpass two different terpene-based conifer defence systems. Beetle growth rate and fecundity were increased when reared exclusively on spruce logs (alternative host) compared to pine logs (native host). Comparative gene expression analysis identified differentially expressed genes (DEGs) related to digestion, detoxification, transporter activity, growth, signalling, and stress response in the spruce-feeding beetle gut. Transporter genes were highly abundant during spruce feeding, suggesting they could play a role in pumping a wide variety of endogenous and xenobiotic compounds or allelochemicals out. Trehalose transporter (TRET) is also up-regulated in the spruce-fed beetle gut to maintain homeostasis and stress tolerance. RT-qPCR and enzymatic assays further corroborated some of our findings. Taken together, the transcriptional plasticity of key physiological genes plays a crucial role after the host shift and provides vital clues for the adaptive potential of bark beetles on different conifer hosts.
Keywords: Host switch; exprese genu; terpeny; Enzyme assay; Weevils; Gene Expression; nosatcovití; Chitin metabolism; Metabolomics; Host adaptation; zvířata; Terpenes; Coleoptera; stanovení celkové genové exprese; brouci; RT-qPCR; Ips sexdentatus; Bark beetles; Animals; Differential gene expression (DGE); Gene Expression Profiling; Detoxification